Assessing public-private-partnerships in South Africa and how administrative law should respond - Zondi, Nokulunga (Department of Public Law, 2019)
In today’s highly globalized and technological societies, it has become more difficult for public entities to maintain high quality public services, especially given recent ecological concerns. Thus, many public entities have turned to privatisation, promising to maintain public service with the efficiency of private companies and markets. Nonetheless, there are clear drawbacks to privatisation, such as the promised public services being drowned out in favour of more profitable schemes. The compromise, here, is the ascension of public-private-partnerships (PPPs), which are agreements in which private entities are bound to maintain certain public services while taking ownership, in limited form, of public property. The concerns of relying on PPPs for utility services are explored in this dissertation. In particular, the case of Eskom taking control of electricity provision in South Africa through a PPP is assessed in the context of a similar arrangement in Germany. It is the conclusion of this dissertation that if administrative law is not responsive to the threats to the impoverished populations in South Africa not having access to electricity, then an infringement of fundamental human rights may occur.